BRIX: A Gamified Application-Based Platform in German Language Learning for Beginners - Desti Nur Aini; Ibrahim Asmorodina; Erin Alida Damayanti (Nusantara Science and Technology Proceedings, 2024)
The landscape of foreign language learning has transformed due to technological advancements and innovative approaches. Among the noteworthy approaches is the integration of game elements, or gamification. Gamification has demonstrated its ability to enhance motivation, engagement, and learning outcomes across various contexts. In the realm of beginner-level German language instruction, the utilization of a gamified application-based platform presents itself as an innovative and effective method. This study is a development study that incorporates gamification elements in German language learning for beginners through an app-based platform called "BRIX". The research methodology comprises several stages, including needs analysis, design, development, implementation, limited trials, and evaluation. Data collection involves language proficiency tests, surveys, and observations of user interactions with the platform. The findings of the study indicate that the utilization of the BRIX platform has a positive impact on the process of learning the German language. Individuals utilizing the BRIX platform tend to demonstrate improvement in understanding grammatical structures, enriching vocabulary skills, and enhancing communication abilities for everyday situations. Additionally, the levels of engagement and motivation among participants are proven to be higher when compared to conventional teaching methods. Several recommendations emerge as valuable guidelines for future research include developing an advanced version. These include the development of an advanced version of the BRIX platform with enhanced interactive features, adjustable difficulty levels, and social integration for user interaction. Furthermore, adapting the BRIX platform for other subjects could provide insights into the effectiveness of gamification across various educational domains.